Bile acid-mediated gut-liver axis crosstalk: the role of nuclear receptor signaling in dynamic regulation of inflammatory networks - Yan, Wenlong; Zhang, Kun; Guo, Jing; Xu, Lingfen (Frontiers in Immunology, 2025)
Bile acids (BAs) are critical mediators of metabolic and immune regulation, influencing both liver and intestinal function. Their homeostasis, maintained through the enterohepatic circulation, is pivotal for immune-metabolic balance. BAs activate key receptors, including Farnesoid X Receptor (FXR) and TGR5, to modulate inflammation. FXR exerts anti-inflammatory effects by suppressing NF-κB signaling and cytokine production, whereas TGR5 primarily regulates NLRP3 inflammasome activation. Dysregulated BA signaling, driven by microbial dysbiosis, exacerbates inflammatory diseases like non-alcoholic fatty liver disease (NAFLD) and inflammatory bowel disease (IBD). This review explores the intricate roles of BAs in inflammation, highlighting the microbiome’s influence on BA metabolism and immune responses. Understanding the BA-immune axis offers new therapeutic avenues for modulating inflammation and improving clinical outcomes in inflammatory diseases.